2001
DOI: 10.1207/s15324826an0804_2
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Complaints, Verbal Fluency, and Working Memory in Mild Multiple Sclerosis

Abstract: Patients with mild multiple sclerosis (MS) regularly report subjective complaints characterized by generalized cognitive inefficiency. A feature of these complaints is reduced verbal fluency, for example, losing the thread of conversation. Mild MS patients and controls were compared on subjective complaints, verbal fluency, and working memory, and the possible role of working memory was investigated. As predicted, subjective difficulties and verbalfluency each correlated with working memory. Subjective difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…While most prior studies have found little or no relationship between these factors (Beatty & Monson, 1991;Benedict, Munschauer, et al, 2003;Lovera et al, 2006;Maor, Olmer, & Mozes, 2001;Taylor, 1990), when the measures of self-reported cognition correspond Correspondence and reprint requests to: Cynthia Honan, School of Psychology, University of New South Wales, NSW, 2052. E-mail: c.honan@ unsw.edu.au closely to the specific cognitive domains being tested, significant relationships have been detected (Chiaravalloti & De Luca, 2003;Goverover, Genova, Hali, Chiaravolloti, & DeLuca, 2014;Matotek, Saling, Gates, & Sedal, 2001;Randolph, Arnett, & Freske, 2004;. In this study, perceived general cognitive problems and prospective memory problems were evaluated separately as measures of perceived cognitive difficulties.…”
Section: Introductionmentioning
confidence: 84%
“…While most prior studies have found little or no relationship between these factors (Beatty & Monson, 1991;Benedict, Munschauer, et al, 2003;Lovera et al, 2006;Maor, Olmer, & Mozes, 2001;Taylor, 1990), when the measures of self-reported cognition correspond Correspondence and reprint requests to: Cynthia Honan, School of Psychology, University of New South Wales, NSW, 2052. E-mail: c.honan@ unsw.edu.au closely to the specific cognitive domains being tested, significant relationships have been detected (Chiaravalloti & De Luca, 2003;Goverover, Genova, Hali, Chiaravolloti, & DeLuca, 2014;Matotek, Saling, Gates, & Sedal, 2001;Randolph, Arnett, & Freske, 2004;. In this study, perceived general cognitive problems and prospective memory problems were evaluated separately as measures of perceived cognitive difficulties.…”
Section: Introductionmentioning
confidence: 84%
“…There is at least some empirical justification for clinician skepticism. While most MS studies have found that self-reported cognitive complaints relate to objective testing (Beatty & Monson, 1991;Benedict et al, 2004;Chiaravalloti & Deluca, 2003;Hoogervorst et al, 2001;Kujala et al, 1996;Maor et al, 2001;Matotek et al, 2001;Randolph et al, 2001Randolph et al, , 2004Taylor, 1990), others have not (Benedict et al, 2003;Gold et al, 2001Gold et al, , 2003. Even among studies with significant findings, the largest reported correlations are often modest (r , .29;Hoogervorst et al, 2001;Maor et al, 2001;Taylor, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The nature, quality, and quantity of deficits found depend on the type of illness studied and the instruments used to investigate cognitive function. For example, whereas multiple sclerosis is sometimes accompanied by a working memory deficit9, 10 and accuracy and speed in everyday activities,11 it is IQ and attentional memory that are more often impaired in sickle cell disease 12, 13. Information processing speed may be reduced in people with diabetes,5 people with chronic fatigue syndrome,8 and in those with systemic lupus erythematosus,14 while hepatitis C sufferers may experience problems with sustained attention and psychomotor speed 15.…”
mentioning
confidence: 99%
“…The latter argument finds support in the work of Blomhoff et al,22 who showed that people with IBS make increased use of attentional resources. Similarly, Matotek et al9 argued that verbal fluency problems in people with multiple sclerosis may also be due to capacity limitations in working memory.…”
mentioning
confidence: 99%